2019
DOI: 10.1053/j.ajkd.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Care and Quality of Life Among Caregivers for Adults Receiving Maintenance Dialysis: A Systematic Review

Abstract: Dialysis is a burdensome and complex treatment for which many recipients require support from caregivers. The impact of caring for people dependent on dialysis on the quality of life of the caregivers has been incompletely characterized. Study Design: Systematic review of quantitative studies of quality of life and burden to caregivers. Setting & Study Population: Caregivers of adults receiving maintenance dialysis. Selection Criteria for Studies: The Cochrane Library, Embase, PsycINFO, CINAHL, PubMed, and MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 65 publications
4
103
0
3
Order By: Relevance
“…A recent systematic review found that few studies have examined the burden of informal caregivers of people undergoing either haemodialysis or peritoneal dialysis (Hoang et al 2018). Informal caregiver burden has been reported as being between medium to high levels (Mollaoglu et al 2013;Avşar et al 2015;Cantekin et al 2016;Gilbertson et al 2018). Informal caregivers, who are young, have higher education levels and spend more time in caring for their family-member with ESKD, reported greater levels of burden (Mollaoglu et al 2013;Bayoumi 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent systematic review found that few studies have examined the burden of informal caregivers of people undergoing either haemodialysis or peritoneal dialysis (Hoang et al 2018). Informal caregiver burden has been reported as being between medium to high levels (Mollaoglu et al 2013;Avşar et al 2015;Cantekin et al 2016;Gilbertson et al 2018). Informal caregivers, who are young, have higher education levels and spend more time in caring for their family-member with ESKD, reported greater levels of burden (Mollaoglu et al 2013;Bayoumi 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advances in the HD treatment of patients with end‐stage renal disease have provided significant improvements in their health, quality of life and survival; however, interventions targeting their caregivers are often neglected. These caregivers are often family members and responsible for providing comprehensive care . Some studies have found high caregiver burden levels assessed from the perspective of the patient and caregiver .…”
Section: Discussionmentioning
confidence: 99%
“…These caregivers are often family members and responsible for providing comprehensive care . Some studies have found high caregiver burden levels assessed from the perspective of the patient and caregiver . In this context, Suri et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations